Recurrence due to dissemination of tumor cells after transoral endoscopic thyroidectomy vestibular approach - Navarro-Fernández, Carlos; Luna-Peteuil, Zelik; Guemes-Meza, Agustin; Luna Ortiz, Kuauhyama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The present report aims to document a case of recurrence attributed to residual tumor in a patient with papillary thyroid cancer who underwent Transoral endoscopic thyroidectomy vestibular approach (TOETVA). A 48-year-old female presented with a mass in the central part of the neck. On ultrasound, the lesion was classified as TIRADS 4b. Fine-needle aspiration biopsy revealed papillary carcinoma (cT1b cN0 cM0, stage I). The patient underwent transoral thyroidectomy without complications. The pathology report showed conventional papillary thyroid carcinoma in both lobes, with the predominant lobe measuring 2×1×0.5 cm. Three years later, the patient presented with elevated thyroglobulin levels (1.92) despite adequate TSH suppression. Six months later, a repeat ultrasound showed continued persistence of the lesion at level VI, prompting resection under local anesthesia, which revealed invasive papillary thyroid carcinoma involving soft tissues. TOETVA remains a safe procedure for cancer cases. However, its oncological outcomes have not yet been fully demonstrated, particularly regarding the impact of possible recurrences stemming from residual tumor fragments or cells during the procedure.